Function and its inverse was graphed.
<u>Step-by-step explanation:</u>
y = -4x²- 2
To find the inverse function of y = -4x²- 2 we have to transform the formula to calculate x in terms of y.
y = -4x²- 2
-4x² = y - 2
x = √(y-2) / -4
Now we can change the letters to follow the convention that x is the independent variable and y is the function's value:
y = √(x-2) / -4
Now we have to draw the graph as,
It was side by side that is LHS is the function and the RHS is its inverse.
Answer:
13 per minute
Step-by-step explanation:
Answer: x2 + 12x
Step-by-step explanation:
Answer:
g
Step-by-step explanation:
Answer:
you do 12 times 3 which equals 36 so 36 is your answer